L’USO DEL DRONE NELLA DOCUMENTAZIONE ARCHEOLOGICA: IL CASTELLO DI MONTEFALCO IN SABINA (RM) - Bernardi, Martina; Fasson, Federico (GEOmedia, 2022)
The continuous progress of digital technologies is leading to a methodological redefinition in archaeology: how to use the new digital tools and software in the field - often low cost - to obtain functional elements for the historical reconstruction of a landscape, site, or building, without invasive investigations. This moment for the archaeological matter could be defined as the era of the “Digital Archeology” for the progress of the new technologies that now it is necessary to connect to the traditional methods of analysis. In recent years, the UAV has become an indispensable instrument for territorial research in archeology, allowing us to create a georeferenced photogrammetric product and 3D digital models in scale. This paper will illustrate the drone use in the castle of Montefalco in Sabina (RM) during the field survey activities promoted by Roma Tre University.